Emerging therapeutic targets in ovarian cancer - Kaye, Stan; Brown, Robert; Gabra, Hani; Gore, Martin (Springer eBooks., 2011)
Despite rapid advances in understanding the biology of ovarian cancer, progress in treatment has been slow. But the prospects for improvement have never been better. A wide range of novel therapeutic targets now present themselves for clinical evaluation and initial results are certainly encouraging. In this text, all these areas are covered by experts in the field. Each chapter provides up-to-date coverage of clinical information, prefaced by a description of the rational basis for the selection of each target area and consideration of biomarkers that can be used to aid clinical evaluation. The four editors work together within the Ovarian Cancer Action collaborative research programme in London and they bring a wealth of laboratory and clinical expertise to this topic. The text should provide an invaluable source of reference for clinical and laboratory-based researchers working to meet the challenges of ovarian cancer.